Identification of the Second Mutation of BADH2 Gene Derived from Rice Mutant Lines Induced by Gamma Rays - I. Ishak (PPIKSN-BATAN, 2016)
The BADH2 gene acts as suppressor of 2-acetyl-1-pyrolline (2AP) biosynthesis in plants. 2AP is the volatile compound which provides fragrance in rice. Biosynthesis of 2AP occurs when BADH2 loses its function as suppressor gene. Aromatic rice cultivars naturally incur mutation of BADH2 gene at 8 bp. In this experiment, aromatic mutant rice lines derived from irradiation of Sintanur cultivar by gamma rays with dose of 100 Gy were studied in molecular level. These mutant lines were characterized at the M10 plant generation under the assumption that genetically these aromatic mutant rice lines were homozygotic. Several primers related to aroma in rice have been used for polymerase chain reaction (PCR) in a thermal cycler instrument. Gel electrophoreses were carried out using 1.5% agarose in TAE buffer. DNA fragments at 254 bp and 355 bp (base pair) were taken and amplified by primer for nucleotide sequencing of these fragments. Molecular identification and characterization after electrophoresis showed that the mutant line from AR1020 can be differentiated from AR.1080 at 254 bp. Nucleotide sequence data from of these DNA fragments showed that point mutations (deletions and substitutions) occurred at the BADH2 gene in exon 7; those are called second mutation and were caused by gamma rays effects. The Sintanur variety was used as check cultivar and its DNA sequence was compared to that of the AR.1020 mutant line. The results from both DNA sequences (from cv. Sintanur and AR.1020) derived from fragments at 254 bp show that point mutations occurred within exon 7 and earlier stop codon occurred in the AR.1020 mutant rice line. Further, the use of EA primer in PCR resulted in detection of deletion and substitution of nucleotides in the AR.1020 mutant line.